A simple method for monitoring springboard reaction force in gymnastic vaulting - Hao, W. Y.; Wu, C. L.; Wang, X. D.; Xiao, D. D.; Wang , Q. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
This work was to found a new method for measuring the reaction force of springboard (BRF), which provides scientific supports to the diagnosis of take-off technique. The elastic moduli of GYMNOVA soft and hard springboards were derived by method of mechanics of material, then the springboards were tested in static, dynamic experiments and computer simulations. An equation with different coefficients for soft and hard spring boards, which describe force-displacement of the springboard, F=kx+cx was obtained and validated. This equation can be used with convenience by employing a high speed camera shooting to the springboard for rapidly monitoring the take-off BRF, and provide scientific supports in the enhancement of vaulting techniques, and in injury preventions as well.